A Danish poverty line? Poverty judgements by students of social work, pedagogy and health services - Monrad, Merete; Ejrnæs, Morten; Fuglsang, Tine (Politica, 2018)
When is a family poor? We examine what factors are emphasized when people judge whether a family is poor or not. The article is based on a factorial survey with 356 respondents who study social work, nursing, nursery teaching and nutrition and health. Based on theories of poverty, we study what aspects of a family’s life situation are accentuated when people judge whether the family is poor or not. The respondents primarily emphasize income in their poverty judgements. Some deprivations also enter into the judgements, while the duration of deprivations, gender and labor market participation have no or minimal significance for the judgements.